Vanadium oxide / carbon-based carbon fiber structure supercapacitor and preparation method thereof
Through the combination of vanadium oxide/carbon-based active material composite electrode and carbon fiber material, the problem of low specific capacitance and energy density of carbon fiber supercapacitors is solved, high specific capacitance and long cycle life are achieved, and low-cost can be achieved through simple processes. Mass production.
Patent Information
- Application Number
- CN202411262223.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The specific capacitance and energy density of carbon fiber structure supercapacitors limit their practical application, and the conductivity and cycle life of vanadium oxide materials are insufficient, limiting their application range.
Using vanadium oxide/carbon-based active material composite electrodes, the combination with carbon fiber materials provides high specific capacitance and energy density by oxidation and reduction reaction of vanadium oxide materials, and the combination of composite electrodes and epoxy resin electrolytes can improve electrochemical performance. and cycle life.
It significantly improves the specific capacitance and energy density of carbon fiber structure supercapacitors, and greatly improves its cycle life. At the same time, the preparation method is simple and low in cost, which is suitable for large-scale production.
Smart Images

Figure CN119170419A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a supercapacitor and a preparation method thereof, and in particular to a supercapacitor with a vanadium oxide / carbon-based active material carbon fiber structure and a preparation method thereof. Background Art
[0002] With the acceleration of global energy transformation and the urgent need for sustainable development, energy storage devices play an increasingly important role in the modern energy system. The research and application of energy storage devices in aerospace, land transportation, rail transportation, maritime transportation and other fields has become an important strategy. Using carbon fiber materials as electrodes to prepare structural energy storage devices can achieve mechanical bearing while also having power storage functions, which can minimize the overall weight of the system and system integration, and is of great significance for realizing the multifunctionality of materials.
[0003] The field of carbon fiber structure energy storage mainly includes carbon fiber structure batteries and carbon fiber structure supercapacitors. Compared with carbon fiber structure batteries, carbon fiber structure supercapacitors have higher power density, faster charging and discharging speed, and longer cycle life. However, the low specific surface area and surface activity of carbon fiber lead to its low specific capacitance and energy density, which limits its practical application. At present, the main method is to load active material coating on the surface of carbon fiber to increase the specific surface area and surface activity of carbon fiber electrode, including carbon-based materials, metal oxides, etc. Carbon-based materials have the advantages of low cost, long cycle life, and high stability, and are widely used in supercapacitors. However, it is difficult to achieve high specific capacitance in carbon-based supercapacitors relying solely on the energy storage mechanism of double-layer capacitance. Metal oxide materials can undergo highly reversible redox reactions on the electrode surface to produce high capacity that is dozens of times higher than the double layer. Among them, vanadium oxide is regarded as a highly potential supercapacitor electrode active material because it has the advantages of wide voltage window, low cost, multiple oxidation states, and can provide high specific capacitance and high energy density in reversible redox reactions. However, its poor conductivity and cycle life limit its application. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a vanadium oxide / carbon-based active material carbon fiber structure supercapacitor with high specific capacitance, energy density and cycle life; the second purpose of the present invention is to provide a method for preparing the vanadium oxide / carbon-based active material carbon fiber structure supercapacitor, which has the advantages of simple process, low cost and large-scale production.
[0005] Technical solution: The vanadium oxide / carbon-based active material carbon fiber structure supercapacitor of the present invention comprises a vanadium oxide / carbon-based active material carbon fiber electrode, wherein the vanadium oxide / carbon-based active material carbon fiber electrode comprises a vanadium oxide material, a carbon-based active material and a carbon fiber material, wherein the vanadium oxide material comprises V2O5, V2O5·nH2O, VO2, H2V3O8, V2O3, V4O9, V6O 13 The carbon-based active material comprises one or more of activated carbon, graphite, graphene, graphene oxide, redox graphene, fullerene, carbon nanospheres, and carbon nanotubes.
[0006] Furthermore, the carbon fiber material includes one or more of T300, T700, T800, and T1000.
[0007] Furthermore, the supercapacitor includes a three-layer structure, wherein the upper and lower layers are both vanadium oxide / carbon-based active material carbon fiber electrodes, the tabs of the upper and lower electrodes are located on the same side, the middle layer is a glass fiber diaphragm, and the side of the vanadium oxide / carbon-based active material carbon fiber electrode coated with vanadium oxide / carbon-based active material is close to the middle layer.
[0008] The method for preparing the vanadium oxide / carbon-based active material carbon fiber structure supercapacitor comprises the following steps:
[0009] (1) preparing a composite electrode active material by compounding a vanadium oxide material and a carbon-based active material;
[0010] (2) preparing an epoxy resin electrolyte solution;
[0011] (3) coating the composite electrode active material on the upper surface of the carbon fiber material, and obtaining a vanadium oxide / carbon-based active material carbon fiber electrode after drying;
[0012] (4) Preparation of supercapacitors.
[0013] Furthermore, the carbon fiber material needs to be pretreated and cut before use, and the pretreatment includes the following steps: impregnating the carbon fiber material with a KOH solution, then washing it with deionized water for multiple times and drying it in an oven; a tab is left on one side of the carbon fiber material after cutting. Furthermore, during the layering, the glass fiber separator needs to be cut into a square with an area slightly larger than the carbon fiber electrode. Furthermore, the drying time in the oven is 2-6 hours, and the drying temperature is 60-100°C.
[0014] Furthermore, in step (1), the vanadium oxide material and the carbon-based active material are compounded and then a conductive agent, a binder and an organic solvent are added and mixed, the mass ratio of the vanadium oxide material to the carbon-based active material is 2-8:8-2, and the mass ratio of the compounded mixture to the conductive agent and the binder is 6-8:3-1:1.
[0015] Furthermore, the conductive agent is graphite, acetylene black or conductive carbon black.
[0016] Furthermore, the binder is polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polyvinyl pyrrolidone (PVP), polytetrafluoroethylene (PTFE) or sodium carboxymethyl cellulose (CMC).
[0017] Furthermore, the organic solvent is N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethylacetamide (DMAC) or acetonitrile.
[0018] Furthermore, the mixing and stirring time is 2-6 hours.
[0019] Furthermore, in step (3), the preparation of the epoxy resin electrolyte solution comprises the following steps:
[0020] The ionic electrolyte and electrolyte salt are mixed in a mass ratio of 3-7:7-3, and an organic solvent is added and stirred. Then two epoxy resins are added in a mass ratio of 3-7:7-3 and stirred. The mass ratio of the mixture of the ionic electrolyte and the electrolyte salt to the mixture of the two epoxy resins is 3-7:7-3. A cross-linking agent is added during the stirring process to obtain an epoxy resin electrolyte solution. Among them, the epoxy resin plays a role in supporting the mechanical properties of the structural supercapacitor as a solid electrolyte.
[0021] Furthermore, the organic solvent is propylene carbonate (PC), ethylene carbonate (EC), ethyl methyl carbonate (EMC) or ethylene glycol dimethyl ether (DEM).
[0022] Furthermore, the epoxy resin is hexahydrophthalic acid diglycidyl ester (HADE), polyethylene glycol diglycidyl ether (PEGDGE) or E51.
[0023] Furthermore, the cross-linking agent is triethylenetetramine (TETA), diethylenetriamine (DETA) or tetraethylenepentamine (TEPA).
[0024] Furthermore, in step (3), the drying temperature is 60-120° C., and the drying time is 8-12 hours.
[0025] Furthermore, in step (4), the step of preparing the supercapacitor includes: layering the vanadium oxide / carbon-based active material carbon fiber electrode and the glass fiber diaphragm, and infiltrating the vanadium oxide / carbon-based active material carbon fiber electrode and the glass fiber diaphragm with an epoxy resin electrolyte solution; and hot-pressing and curing the vanadium oxide / carbon-based active material carbon fiber electrode and the glass fiber diaphragm to obtain a supercapacitor.
[0026] Furthermore, the temperature of the hot pressing curing molding is 50-150° C. and the pressure is 100-1000 Kpa.
[0027] Principle of the invention: The present invention uses vanadium oxide / carbon active material-based composite electrode active materials to prepare carbon fiber structure supercapacitors. Since vanadium oxide can provide high specific capacitance and high energy density through redox reactions, and carbon-based active materials have excellent cycle performance. The synergistic effect of the two can greatly improve the electrochemical performance of carbon fiber structure supercapacitors, while effectively improving the cycle life of carbon fiber structure supercapacitors.
[0028] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The carbon fiber structure supercapacitor has higher specific capacitance and energy density, and greatly improves its cycle life; (2) The preparation method has the advantages of simple process, low cost, and suitability for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The SEM image of the vanadium pentoxide / activated carbon fiber electrode prepared in Example 1; wherein (a), (b), and (c) are SEM images at scales of 20 μm, 5 μm, and 1 μm, respectively;
[0030] Figure 2 is the XRD pattern of the vanadium pentoxide / activated carbon fiber electrode prepared in Example 1;
[0031] Figure 3 The SEM images of the vanadium pentoxide carbon fiber electrode and the activated carbon carbon fiber electrode prepared in Comparative Example 1 and Comparative Example 2; wherein (a) is the SEM image of the vanadium pentoxide carbon fiber electrode prepared in Comparative Example 1, and (b) is the SEM image of the activated carbon carbon fiber electrode prepared in Comparative Example 2;
[0032] Figure 4 CV curves of vanadium pentoxide / activated carbon fiber electrodes prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 at a scan rate of 100 mV / s;
[0033] Figure 5 The vanadium pentoxide / activated carbon fiber electrodes prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 were tested at 5 mA / cm2 Constant current charge and discharge curves under current density;
[0034] Figure 6 The constant current charge and discharge curves of the vanadium pentoxide / activated carbon fiber structure supercapacitor in Example 1 at different current densities;
[0035] Figure 7 This is a graph showing 4000 cycles of the vanadium pentoxide / activated carbon fiber structure supercapacitor in Example 1. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0037] Example 1
[0038] (1) Use 1.85mol / L KOH solution to soak the carbon fiber T300 material and put it in a fume hood for 12 hours. Then use deionized water to wash it several times to remove the residual KOH solution. Put it in an 80℃ oven and dry it for 2 hours to obtain the pretreated carbon fiber material. Cut the carbon fiber material into a 40mm×40mm square, leaving a 20mm×10mm pole ear on one side of the square.
[0039] (2) Vanadium pentoxide (V2O5) and activated carbon (AC) are compounded in a mass ratio of 5:5, the compounded mixture is mixed with conductive agent graphite and binder PVDF in a mass ratio of 7:2:1, and DMF organic solvent is added for stirring to obtain a vanadium pentoxide / activated carbon composite electrode active material.
[0040] (3) The ionic electrolyte EMIM-TFSI and the electrolyte salt LiTSFI were mixed in a mass ratio of 5:5, and the organic solvent PC was added and stirred. Then, PEGDGE and HADE epoxy resins were added in a mass ratio of 5:5 and stirred. The mass ratio of the mixture of the ionic electrolyte and the electrolyte salt to the mixture of the two epoxy resins was 5:5. During the stirring process, the crosslinking agent TETA was added to obtain an epoxy resin electrolyte solution.
[0041] (4) Using a casting machine, the vanadium pentoxide / activated carbon composite electrode active material is cast on the upper surface of the pretreated carbon fiber material and vacuum dried in a vacuum drying oven at 80°C for 12 hours to obtain a vanadium pentoxide / activated carbon fiber electrode.
[0042] (5) Cut the glass fiber into 60 mm × 60 mm squares. Lay the vanadium pentoxide / activated carbon carbon fiber electrode and the glass fiber separator. The upper and lower layers are both vanadium pentoxide / activated carbon carbon fiber electrodes, the tabs of the upper and lower carbon fiber electrodes are on the same side, and the middle layer is a glass fiber separator. The side of the carbon fiber electrode coated with the vanadium pentoxide / activated carbon composite electrode active material is close to the middle layer glass fiber separator. Use epoxy resin electrolyte solution to fully infiltrate the vanadium pentoxide / activated carbon carbon fiber electrode and the glass fiber separator.
[0043] (6) Using a hot press machine, the vanadium pentoxide / activated carbon fiber electrode and the glass fiber separator are hot pressed and solidified, and the hot pressing and solidification temperature is 80° C. and the pressure is 500 KPa. A vanadium pentoxide / activated carbon fiber structure supercapacitor is obtained.
[0044] Example 2
[0045] The supercapacitor preparation process is the same as that of Example 1, except that vanadium pentoxide and activated carbon are compounded in a mass ratio of 7.5:2.5 to prepare a vanadium pentoxide / activated carbon composite electrode active material.
[0046] Example 3
[0047] The supercapacitor preparation process is the same as that of Example 1, except that vanadium pentoxide and activated carbon are compounded in a mass ratio of 2.5:7.5 to prepare a vanadium pentoxide / activated carbon composite electrode active material.
[0048] Comparative Example 1
[0049] The preparation process of the supercapacitor is the same as that of Example 1, except that vanadium pentoxide and activated carbon are compounded in a mass ratio of 10:0, that is, vanadium pentoxide is used as the electrode active material.
[0050] Comparative Example 2
[0051] The preparation process of the supercapacitor is the same as that of Example 1, except that vanadium pentoxide and activated carbon are compounded in a mass ratio of 0:10, that is, activated carbon is used as the electrode active material.
[0052] Figure 1 : This is a SEM image of the vanadium pentoxide / activated carbon fiber electrode prepared in Example 1. The SEM of the vanadium pentoxide / activated carbon fiber electrode prepared in Example 1 was analyzed. Figure 1 As can be seen from (a) and (b), the vanadium pentoxide / activated carbon composite electrode active material is uniformly loaded on the carbon fiber surface. Figure 1 As can be seen in (c), vanadium pentoxide and activated carbon are uniformly mixed, and the small-sized spherical graphite conductive agent forms a conductive network to connect the larger-sized vanadium pentoxide and activated carbon.
[0053] Figure 2 This is the XRD pattern of the vanadium pentoxide / activated carbon carbon fiber electrode prepared in Example 1. The diffraction peaks of the vanadium pentoxide and activated carbon composite electrode active material are in good agreement with the diffraction peaks of the standard vanadium pentoxide XRD card and the standard activated carbon XRD card.
[0054] Figure 3 The SEM graphs of the vanadium pentoxide carbon fiber electrode and the activated carbon carbon fiber electrode prepared in Comparative Example 1 and Comparative Example 2 are shown. (a) is the vanadium pentoxide carbon fiber electrode prepared in Comparative Example 1, and (b) is the activated carbon carbon fiber electrode prepared in Comparative Example 2. It can be seen that the vanadium pentoxide has a layered structure, while the activated carbon has a block structure.
[0055] The electrochemical properties of the carbon fiber structure supercapacitors prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 were analyzed. The results are as follows: Figure 4 , Figure 5 shown.
[0056] Figure 4 The CV curves of the vanadium pentoxide / activated carbon carbon fiber electrodes prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 at a scan rate of 100 mV / s are shown. It can be seen that the CV curve of the V2O5 carbon fiber electrode shows a clear redox peak, showing the properties of a pseudocapacitor, while the CV curve of the AC carbon fiber electrode is close to a rectangle, showing the properties of a double-layer capacitor. As the proportion of V2O5 decreases, the redox peak gradually disappears, and the CV curve gradually approaches a rectangle. Among them, the CV curve of the carbon fiber electrode with V2O5 / AC=5:5 prepared in Example 1 has the largest coverage area and exhibits the best electrochemical performance.
[0057] Figure 5 The active vanadium pentoxide / activated carbon fiber electrodes prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 were tested at 5 mA / cm 2 Constant current charge and discharge curve under current density. It can be seen that compared with the pure V2O5 carbon fiber electrode and the pure AC carbon fiber electrode in Comparative Example 1 and Comparative Example 2, the carbon fiber electrode prepared by compounding V2O5 and AC has a longer discharge time and improved electrochemical performance. The V2O5 / AC=5:5 carbon fiber electrode prepared in Example 1 has the longest discharge time and shows the highest capacitance, which is better than the V2O5 / AC=7.5:2.5 carbon fiber electrode prepared in Example 2 and the V2O5 / AC=2.5:7.5 carbon fiber electrode prepared in Example 3, as well as the vanadium pentoxide electrode prepared in Comparative Example 1 and the activated carbon electrode prepared in Comparative Example 2.
[0058] Figure 6 The constant current charge and discharge curves of the vanadium pentoxide / activated carbon fiber structure supercapacitor prepared in Example 1 at different current densities. 2 At a current density of 0.01 mA / cm, the discharge time of the vanadium pentoxide / activated carbon fiber structure supercapacitor exceeds 25,000 s. As the current density increases, the charge and discharge time gradually decreases. 2 The current density of vanadium pentoxide / activated carbon fiber structure supercapacitor has an area specific capacitance of 172.6mF / cm 2 , the energy density reaches 215.75mwh / kg. The results show that the vanadium pentoxide / activated carbon fiber structure supercapacitor has excellent electrochemical performance.
[0059] Figure 7 This is a 4000 cycle graph of the vanadium pentoxide / activated carbon carbon fiber structure supercapacitor in Example 1. The capacitance retention rate of the structure supercapacitor slightly decreased in the first 1000 cycles, and the capacitance retention rate exceeded 100% at 2000 cycles, which is related to the activation of the electrode active material. After 4000 cycles, the capacitance retention rate can reach 97.69%. The results show that the vanadium pentoxide / activated carbon carbon fiber structure supercapacitor has an excellent cycle life.
Claims
1. A vanadium oxide / carbon-based active material carbon fiber structure supercapacitor, characterized in that: The invention comprises a vanadium oxide / carbon-based active material carbon fiber electrode, wherein the vanadium oxide / carbon-based active material carbon fiber electrode comprises a vanadium oxide material, a carbon-based active material and a carbon fiber material, wherein the vanadium oxide material comprises V2O5, V2O5·nH2O, VO2, H2V3O8, V2O3, V4O9, V6O 13 The carbon-based active material comprises one or more of activated carbon, graphite, graphene, graphene oxide, redox graphene, fullerene, carbon nanospheres, and carbon nanotubes.
2. The vanadium oxide / carbon-based active material carbon fiber structure supercapacitor according to claim 1, characterized in that: The carbon fiber material includes one or more of T300, T700, T800 and T1000.
3. The vanadium oxide / carbon-based active material carbon fiber structure supercapacitor according to claim 1, characterized in that: The supercapacitor includes a three-layer structure, wherein the upper and lower layers are both vanadium oxide / carbon-based active material carbon fiber electrodes, and the pole ears of the upper and lower electrodes are located on the same side, the middle layer is a glass fiber diaphragm, and the side of the vanadium oxide / carbon-based active material carbon fiber electrode coated with vanadium oxide / carbon-based active material is close to the middle layer.
4. A method for preparing a vanadium oxide / carbon-based active material carbon fiber structure supercapacitor according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) preparing a composite electrode active material by compounding a vanadium oxide material and a carbon-based active material; (2) preparing an epoxy resin electrolyte solution; (3) coating the composite electrode active material on the upper surface of the carbon fiber material, and obtaining a vanadium oxide / carbon-based active material carbon fiber electrode after drying; (4) Preparation of supercapacitors.
5. The method for preparing a vanadium oxide / carbon-based active material carbon fiber structure supercapacitor according to claim 4, characterized in that: The carbon fiber material needs to be pretreated and cut before use, and the pretreatment includes the following steps: impregnating the carbon fiber material with a KOH solution, then washing it with deionized water for multiple times and drying it in an oven; leaving a pole ear on one side of the carbon fiber material after cutting.
6. The method for preparing a vanadium oxide / carbon-based active material carbon fiber structure supercapacitor according to claim 4, characterized in that: In step (1), the vanadium oxide material and the carbon-based active material are compounded and then a conductive agent, a binder and an organic solvent are added and mixed. The mass ratio of the vanadium oxide material to the carbon-based active material is 2-8:8-2, and the mass ratio of the compounded mixture to the conductive agent and the binder is 6-8:3-1:
1.
7. The method for preparing a vanadium oxide / carbon-based active material carbon fiber structure supercapacitor according to claim 4, characterized in that: In step (2), the preparation of the epoxy resin electrolyte solution comprises the following steps: The ionic electrolyte and the electrolyte salt are mixed in a mass ratio of 3-7:7-3, and an organic solvent is added for stirring; then two epoxy resins in a mass ratio of 3-7:7-3 are added thereto, and a cross-linking agent is added during the stirring process to obtain an epoxy resin electrolyte solution.
8. The method for preparing a vanadium oxide / carbon-based active material carbon fiber structure supercapacitor according to claim 4, characterized in that: In step (3), the drying temperature is 60-120° C. and the drying time is 8-12 hours.
9. The method for preparing a vanadium oxide / carbon-based active material carbon fiber structure supercapacitor according to claim 4, characterized in that: In step (4), the steps of preparing the supercapacitor include: laying down the vanadium oxide / carbon-based active material carbon fiber electrode and the glass fiber diaphragm, infiltrating the vanadium oxide / carbon-based active material carbon fiber electrode and the glass fiber diaphragm with an epoxy resin electrolyte solution; hot pressing and curing the vanadium oxide / carbon-based active material carbon fiber electrode and the glass fiber diaphragm to obtain a supercapacitor.
10. The method for preparing a vanadium oxide / carbon-based active material carbon fiber structure supercapacitor according to claim 9, characterized in that: The temperature of the hot pressing curing molding is 50-150° C. and the pressure is 100-1000 Kpa.
Citation Information
Patent Citations
Preparation method and application thereof for vanadium pentoxide / oxidized graphene composite film
CN106941049A
Carbon fiber structure supercapacitor based on carbon-based active material and batch preparation method thereof
CN118173389A
Visual supercapacitor electrode and preparation method thereof
CN118263037A
